(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
This article analyzes peculiar manifestation of the art and artist concepts in the short story «Mystery of our Princess» written by Ukrainian writer of the late XIX – early XX centuries Lyubov Yanovsky. This paper focuses on the combination of modernist and populist approaches in disclosing the figure of the artist and art essense and objectives. This reserch reveals the following aspects of the above mentioned concepts: art as an absolute value, talent and the cost of itsimplementation. The author covers gender problems and represents different traits of artist psychology and art creativity psychology in general. The article states that the art and artist concepts in the story of Lyubov Yanovska are an interdisciplinary and relevant to the literary context of the athor’s times.